Isolation of Pancreatic Progenitor Cells with the Surface Marker of Hematopoietic Stem Cells. (20th December 2012) - Ma, Fengxia; Chen, Fang; Chi, Ying; Yang, Shaoguang; Lu, Shihong; Han, Zhongchao
Abstract : To isolate pancreatic progenitor cells with the surface markers of hematopoietic stem cells, the expression of stem cell antigen (Sca-1) and c-Kit and the coexpression of them with pancreatic duodenal homeobox-1 (PDX-1), neurogenin 3 (Ngn3), and insulin were examined in murine embryonic pancreas. Then different pancreatic cell subpopulations were isolated by magnet-activated cell sorting. Isolated cells were cultured overnight in hanging drops. When cells formed spheres, they were laid on floating filters at the air/medium interface. With this new culture system, pancreatic progenitor cells were induced to differentiate to endocrine and exocrine cells. It was shown that c-Kit and Sca-1 were expressed differently in embryonic pancreas at 12.5, 15.5, and 17.5 days of gestation. The expression of c-Kit and Sca-1 was the highest at 15.5 days of gestation. c-Kit rather than Sca-1 coexpressed with PDX-1, Ngn3, and insulin. Cells differentiated from c-Kit-positive cells contained more insulin-producing cells and secreted more insulin in response to glucose stimulation than that from c-Kit-negative cells. These results suggested that c-Kit could be used to isolate pancreatic progenitor cells and our new culture system permitted pancreatic progenitor cells to differentiate to mature endocrine cells.